THE USE OF MIND MAPPING TECHNIQUE TO IMPROVE THE STUDENTS’ WRITING SKILL ON DESCRIPTIVE TEXT AT THE TENTH GRADE OF SMA PGRI LARANGAN PAMEKASAN - Fujiono Fujiono (DIDAKTIKA, 2016)
This study is categorized as a classroom action research (CAR). This study proposed the use of mind mapping technique to improve the students’ writing skill on descriptive text at the tenth grade of SMA PGRI Larangan Pamekasan. The instruments of this study consisted of a scoring rubric for students’ writing skill on descriptive text, questionnaires and observation checklist. The participants of the study were 20 students at the tenth grade of SMA PGRI Larangan Pamekasan. In preliminary study, the students ‘ writing skill on descriptive text and students’ motivation were still low, it was indicated that 5 students or 25% of the students passed the minimum standard achievement/KKM (76). Therefore, the researcher tried to apply the mind mapping technique to improve the students’ writing skill on descriptive text, he found the Students’ interest in learning English , students’ activeness, students’ confidence in writing. But, most students had difficulities dealing with grammar usage and less vocabularies, it was indicated in the first cycle that 9 students or 45% of the students passed the minimum standard achievement/KKM (76). Then, the second cycle would be done by revising the teaching strategy in cycle one that stated in lesson plan by considering the students’ weaknesses they made on the writing test before. In the second cycle was proven that 16 students or 80% of the students passed the minimum standard achievement/KKM (76), and the researcher stated that the students gave better respond in the second cycle than in the first cycle, more students in the second cycle were motivated so that the classroom was more active during the class. So, the results of this research stated that the use of mind mapping technique could improve the students’ writing skill on descriptive text, and class more motivated and enjoyable.